2016
DOI: 10.1038/srep22278
|View full text |Cite
|
Sign up to set email alerts
|

Second magnetization peak effect, vortex dynamics and flux pinning in 112-type superconductor Ca0.8La0.2Fe1−xCoxAs2

Abstract: Investigation of vortex pinning and its relaxation is of great importance for both basic physics and technological applications in the field of superconductivity. We report a great improvement of superconducting properties in the recently discovered 112-type superconductors (Ca, La)FeAs2 through Co co-doping. High critical current density Js(5 K) > 2*106 A/cm2 is obtained and pronounced second peak effect is observed in magnetization hysteresis loops. Both the dynamic and static relaxation studies result in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 56 publications
10
93
3
Order By: Relevance
“…4b. The fishtail effect has been observed in a wide variety of materials, including low-temperature superconductors, cuprates, MgB 2 , and iron-based superconductors 44,45 and associated with an equally wide variety of effects, including elastic-to-plastic crossovers, vortex order-disorder phase transitions, and vortex lattice structural transitions 44 . In fact, a previous study 46 reported the appearance of a fishtail in a pristine NbSe 2 crystal when the applied field was tilted 30° from the c -axis and attributed it to a vortex order-disorder transition.…”
Section: Resultsmentioning
confidence: 99%
“…4b. The fishtail effect has been observed in a wide variety of materials, including low-temperature superconductors, cuprates, MgB 2 , and iron-based superconductors 44,45 and associated with an equally wide variety of effects, including elastic-to-plastic crossovers, vortex order-disorder phase transitions, and vortex lattice structural transitions 44 . In fact, a previous study 46 reported the appearance of a fishtail in a pristine NbSe 2 crystal when the applied field was tilted 30° from the c -axis and attributed it to a vortex order-disorder transition.…”
Section: Resultsmentioning
confidence: 99%
“…However, in superconductors also vortex dynamics leads to a time-dependent magnetization, hence complicating the analysis [48]. Nevertheless, as demonstrated previously for EuFe(As 1−x P x ) 2 [14], both phases can be separated by their opposite signs in the time-dependent behavior (for instance in the FCH-FCC curve, the difference between field-cooled heating and field-cooled cooling curves).…”
Section: A Evidence For a Spin Glassmentioning
confidence: 89%
“…On the other hand, it has been also shown that the overall pinning properties of Fe-based superconductors have been successfully explained in terms of collective pinning and vortex creep [29][30][31][32][33][34]45,73]. Based on these considerations, in this section, we apply the collective pinning and creep model to our results and extract the trend in the dopingdependent Jc.…”
Section: Temperature Dependence Of Jcmentioning
confidence: 95%
“…(3) The second magnetization peak (SMP) in the MHL, characterized by a hump far below Hc2, is evident in most cases, which supports a high Jc of Fe-based superconductors under high magnetic fields. As for the origin of SMP, (i) a crossover from elastic creep to plastic creep [29][30][31][32][33][34] or (ii) the corresponding orderdisorder transition of the vortex lattice [35,36], (iii) a phase transition between a rhombic (at low H) and a high-H square vortex lattice [25,37,38], etc. have been put forth.…”
Section: Introductionmentioning
confidence: 99%